Apego ao lugar em ambiente transitório e as relações de estudantes de psicologia com a universidade: os casos de São Paulo (Brasil) e A Coruña (Espanha) - Silvestri, Patricia Rebello (2024)
We consider the university to be a transitional environment that provides opportunities for professional and personal training. The general aim of the research was to understand the possible process of students becoming attached to this space in the light of environmental psychology, with a view to promoting mental health. The participants were non-resident students in both cities, regularly enrolled in undergraduate courses in Psychology and postgraduate students in Clinical Psychology, at the PUC SP Campus and at the UDC (University of A Coruña - Spain), regardless of age and gender, who were interested in the subject and were willing to participate by signing the Informed Consent Form (ICF). The procedure for data collection was carried out in the following stages at both universities: (1st) initial survey of the approach to the fields carried out in the classroom; (2nd) Application of the Attachment to Place Scale (EAL), application of the Empathy Inventory (IE), original in Spanish and in the version adapted to Portuguese, followed by (3rd) Drawings and semi-structured interview which lasted approximately 30 minutes. The study used a mixed method, which includes both quantitative analyses using instruments and qualitative analysis in the drawings and interviews. The results on place attachment, using the EAL scale, allowed us to understand the human relationships we establish with space: and pointed to proximities in the production of knowledge in Environmental Psychology, highlighting the understanding that people relate to it in an effective way and those relationships play an important role in this relationship. With the Empathy construct, the quantitative results show that there is a moderate relationship in relation to the Affective Sensitivity categories, both in Brazil and Spain. As the capacity for perspective-taking in the Affective Sensitivity dimension evolves, other empathic feelings could be formed. We believe that it is necessary to look for strategies to develop resources to help students cope with new situations, which can be carried out by services and professionals, who can help students in their self-knowledge and/or in coping with their difficulties, thus increasing their ability to respond more satisfactorily to the challenges faced in this important and significant phase of life. We hope that this research will motivate other studies on transitional environments with university students. This work was carried out with the support of the Coordination for the Improvement of Higher Education Personnel (CAPES) - Brazil - Funding Code 001